Converge Transforming Business at the Intersection of Marketing and Technology - Lord, Bob (John Wiley & Sons, Incorporated, 2013)
The leaders of Razorfish share their strategies for merging marketing and IT To create rich, technologically enabled experiences, enterprises need close collaboration between marketing and IT. Converge explains how the merging of technology, media, and creativity is revolutionizing marketing and business strategy. The CEO and CTO of Razorfish, one of the world's largest digital marketing agencies, give their unique perspective on how to thrive in this age of disruption. Converge shares their first-hand experience working closely with global brands-including AXE, Intel, Samsung, and Kellogg-to solve business problems at the collision point between media, technology, and marketing. With in-depth looks at cloud computing, data- and API-enabled creativity, ubiquitous computing, and more, Converge presents a roadmap to success. Explains how to organize for innovation within your own organization by applying the principles of agile development across your business Details how to create a religion around convergence, explaining how to tell the story throughout the organization Outlines how to adapt processes to keep up with and take advantage of rapid technological change A book by practitioners for practitioners, Converge is about rethinking business organizations for a new age and empowering your people to thrive in a brand, new world